Journalism in the Twenty-First Century - Canavilhas, João (2018)
Transmedia content has been the subject of several studies in the feld of fction, sustaining relative unanimity about the characteristics that this kind of content should have. In the feld of journalism, the situation is fairly diﬀerent due to its particular specifcities. Multimedia, intermedia, or cross-media are often wrongly used as synonymous of transmedia, although there are important diﬀerences between all these concepts. In part, this misunderstanding is motivated by the fact that all of them relate to convergence processes in journalism, but a more detailed analysis allows us to fnd diﬀerences, highlighting transmedia as the most complete concept. This chapter proposes a framework that can support journalists in the production of transmedia contents that conveniently explore the characteristics of the involved media, using formats and languages that better ft the story, and enabling the user to engage in the interpretation, change, and distribution of these contents